The Positive And Negative Effects Of Dump Sites On Economic Livelihood Of People. A Case Study Of The Abokobi Dump Site - Dawaare, T. (University of Ghana, 2014)
Globally, developing economies have relatively high production and consumption patterns which produce huge amounts of waste which normally ends up at dump sites. This study therefore sorts to identify further the positive and negative effects of the Abokobi dump site on livelihood. In all, 122 respondents were interviewed using self administered questionnaires and interviews. They were made up of 60 waste pickers, 60 non waste pickers and two officers, one each from the municipal assembly and the Abokobi dump site. The Drivers, Pressures, State, Impact and Response framework was used in the analysis to assess the dump site and its effects on livelihoods in four thematic areas; Factors that serve as drivers at the Abokobi dump site, resulting pressures and state of the dump site, Impacts of the dump site to livelihoods and Measures undertaken as a response to minimise management of dump sites. Results of the study showed that the Abokobi dump site is managed by the Zoomlion Waste Management Company and management is done with the use of a bulldozer, a compactor and an excavator therefore burning of refuse is not a method of management but happens as a result of combustion of gasses. The dump site aids in the breeding of mosquitoes, houseflies and rodents aside the air pollution and all these pose negative effects on livelihood but it again serves the livelihood of waste pickers. As a recommendation to the study, a composting facility should be constructed at the dump site which will be responsible for turning waste into other products such as fertilizers and that capping of gases in order to ensure a balanced situation between non waste pickers and waste pickers.
Thesis (MA)
Keywords: Positive; Negative; Dump Sites; Economic Livelihood; People; Abokobi Dump Site; Accra; Ghana